Sustainable industrial policies and strategies in the textiles and clothing sector: Lessons learned from Cambodia, Jordan and Viet Nam - Stacey Frederik (International Labour Organization (ILO), 2024)
Countries are increasingly adopting industrial strategies and policies in response to global crises and emerging economic trends. With regards to the textiles and clothing sector, industrial strategies and policies, when developed in an inclusive manner, can address economic, social and environmental concerns. This paper summarizes and analyses textiles and clothing strategies developed in Cambodia, Jordan and Viet Nam. It sets out recommendations for the development of holistic industrial policies for the sector. In addition, it provides guidance on the inclusion of a diverse range of stakeholders during this process.
Keywords: 330; Industrial policy; Textile industry; Garment industry; Corporate social responsibility; Jordan; Cambodia; Vietnam; Industriepolitik; Textilindustrie; Bekleidungsindustrie; Corporate Social Responsibility; Jordanien; Kambodscha; Vietnam